Cover Image, Volume 84, Issue 11. Issue 11 (20th October 2016) - Lu, Cheng; Stock, Gerhard; Knecht, Volker
Abstract : The cover image, by Volker Knecht et al., is based on the Article Mechanisms for allosteric activation of protease DegS by ligand binding and oligomerization as revealed from molecular dynamics simulations, DOI:10.1002/prot.25154 .